LINKING STRATEGIC HUMAN RESOURCE MANAGEMENT, - Kankaanpää, Suvi (My University, 2017)
Leaders have lately realized that innovation and competitive edge is easier and cheaper to source within the organization than try to outsource. Knowledge is seen as capital of the organizations and leaders are keen to capitalize it. Many organizations, private as well as public ones has the need to or have tried im-plement knowledge management practices. Many of them have failed. This thesis looks into knowledge management theory and to the theories of organizational culture, strategic human resource management and organizational learning which all support each other. The aim is to connect the theories on theoretical level as well as empirical level to be able to establish the best practices and learn why some of the organi-zations struggle to implement knowledge management. In addition, the empirical part is formed from twelve previously made case studies from around the world which prove the connection in the empirical level. The theoretical framework is based on the theories of knowledge management including the two types of knowledge, tacit and explicit, knowledge transfer and knowledge creation, the theory of organizational learning, learning organization and organizational memory, the theory of strategical human resource management and the activities, and the theory of organizational culture, the types of organizational cul-ture and how type affects on the employees. The research method is literature review with twelve case studies that are done by researchers in the pub-lic and private organizations around the world. The case studies have been sourced from scientific mana-gerial publications trough Tritonia network. The findings were that the previously mentioned methods are in fact connected. Furthermore, the case studies confirm that strategically defined goals and organizational culture are the influential aspects why some organizations succeed and others fail in implementation of knowledge management. Without proper implementation of culture that empowers employees and guarantees openness and motivation by incen-tives create positive environment for free flow of knowledge. Knowledge can be seen as power especially in public organizations that are hierarchical and bureaucratic. In addition, the strategic human resource management functions and free flow of knowledge are the other key components. Implementation of knowledge management is a process that requires active managers and right type of organizational learn-ing actions. The first step is identification of strategical targets and organizational culture, if the culture as it is does not facilitate the desired outcome it needs to be changed first, change is possible but time con-suming. The second step is to support the culture with strategical human resource management activities. Step three is to implement and safe guard knowledge transfer so that it becomes continuous organization-al learning, and then the activities are imprinted to organizational memory and are more easily transferred from old to new employees.
Keywords: Knowledge Management; Organizational Culture; Organizational Learning; Strategic Human Resource Management; fi=Julkisjohtaminen|en=Public Management |; fi=Master's Degree Programme in Intercultural Studies in Communication and Administration|